Associations between the smoking‐relatedness of a cancer type, cessation attitudes and beliefs, and future abstinence among recent quitters - Martínez, Úrsula (Psychooncology, 2018)
OBJECTIVE: Smoking after a diagnosis of cancer can negatively impact treatment outcomes and quality of life. It is important that patients quit smoking and remain abstinent regardless of cancer type. Some cancer types (eg, lung) have stronger links to smoking as a cause than do others (eg, colorectal). The aims of this study were to (1) assess associations between smoking‐relatedness of the cancer type with beliefs and attitudes concerning smoking abstinence (eg, confidence, self‐efficacy), and (2) assess these variables as predictors of future abstinence. METHODS: In this secondary analysis, cancer patients (N = 357) who quit smoking within the previous 90 days were assigned a code of 3, 2, or 1 according to the cancer type’s level of smoking‐relatedness: Very related (n = 134, thoracic and head and neck), Somewhat related (n = 93, acute myeloid leukemia, bladder, cervix, colorectal, esophageal, kidney, liver, pancreas, and stomach), and Unlikely related (n = 137, all other cancer types). RESULTS: Smoking‐relatedness was positively associated with plan to stay smoke‐free, maximum confidence in being smoke‐free in 6 months, higher abstinence self‐efficacy, and lower expected difficulty in staying smoke‐free. Each of the 4 beliefs and attitude variables predicted abstinence 2 months later. Smoking‐relatedness also predicted abstinence in a univariate model, but not in a multivariable model with the belief and attitude variables. Using backwards stepwise procedures, the final model included plan to stay smoke‐free, confidence in being smoke‐free, and abstinence self‐efficacy. CONCLUSION: These results are consistent with our conceptualization of cessation motivation differing by smoking‐relatedness of the cancer type and predicting future abstinence.